Se-doped Zintl phase thermoelectric material and preparation method thereof

By doping 0.04 Se element in BaCu2Te2 material, BaCu2Te1.96Se0.04 thermoelectric material was prepared, which solved the problems of high thermal conductivity and low electrical conductivity of BaCu2Te2 material, and significantly improved its thermoelectric conversion efficiency and ZT value.

CN119698216APending Publication Date: 2025-03-25GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795528.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

BaCu2Te2 material has a high thermal conductivity and low electrical conductivity, which leads to its low thermoelectric conversion efficiency, limiting its application in the field of thermoelectric materials.

Method used

Doping Se element at 0.04 at the Te position of BaCu2Te2 material, the Zintl phase thermoelectric material BaCu2Te1.96Se0.04 was prepared through solid phase reaction and hot pressing process to optimize its thermoelectric properties.

Benefits of technology

After doping Se element, the thermal conductivity and electrical conductivity of the material are reduced, which significantly improves its power factor, and nearly doubles the ZT value, optimizing the thermoelectric performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698216A_ABST
    Figure CN119698216A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and discloses a Se-doped Zintl phase thermoelectric material and a preparation method thereof, and the preparation method comprises the following steps: S1, smelting a Ba ingot; s2, Ba ingots, Cu strips, Te blocks and Se powder are weighed according to the proportion of 1: 2: 1.96: 0.04 and put into a reaction container; s3, carrying out solid-phase reaction; s4, sampling and grinding to obtain fine powder; s6, putting the powder into a crucible, and then putting the crucible into a glass tube; s7, annealing in a muffle furnace; s8, sampling and grinding are carried out, fine black powder is obtained, the powder is sintered into a solid, and BaCu2Te1. 96Se0. 04 is obtained; by doping the Se element at the Te position of the thermoelectric material BaCu2Te2, the power factor of the material is improved, and the thermal conductivity of the material is further reduced, so that the thermoelectric performance of the material is optimized, and the thermoelectric conversion efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to a Se-doped Zintl phase thermoelectric material and a preparation method thereof. Background Art

[0002] With the rapid development of global industry, people's demand for electricity by burning fossil fuels is also increasing significantly. However, in the process of fossil fuel combustion, most of the energy will be released into the environment in the form of waste heat, leading to environmental problems such as global warming and climate change. These fossil fuels are non-renewable resources, so energy shortages and environmental pollution have become issues that cannot be ignored in every country. Thermoelectric materials can realize thermoelectric conversion and have the advantages of safety, energy saving, and environmental protection, so they have attracted much attention. Thermoelectric devices made of thermoelectric materials have the advantages of small size, light weight, no noise, no vibration, no mechanical parts, precision and reliability, and no pollution to the environment. They have important application value and broad application prospects in the fields of temperature difference power generation and thermoelectric refrigeration.

[0003] High-performance thermoelectric materials need to have both high electrical transport performance and low thermal transport performance. However, the strongly coupled electroacoustic properties make it very difficult to regulate the transport of electrons or phonons alone, which is also the main reason that limits the improvement of thermoelectric figure of merit. In 1995, Slack proposed a design criterion for thermoelectric materials based on basic physical properties, believing that good thermoelectric materials should have glass-like thermal conductivity and single crystal-like electrical properties, namely "phonon glass-electron crystal" (PGEC). Under the guidance of this theory, people have discovered materials with "phonon glass-electron crystal" characteristics such as filled skutterudite compounds and intermetallic complexes, and have achieved excellent thermoelectric performance. Among them, Zintl phase alloys have low intrinsic lattice thermal conductivity due to their complex crystal structure. At the same time, the covalent grid in the crystal provides a good channel for electrical transport, which is a very promising class of thermoelectric materials.

[0004] Compared with other Zintl materials, 1-2-2Zintl phase BaCu2Te2 material is an ideal thermoelectric material due to its complex internal bonding structure and crystal structure. However, the thermal conductivity of BaCu2Te2 material itself is high and the electrical conductivity is low. In general, the ZT is low, which limits the thermoelectric conversion efficiency of BaCu2Te2 material. Summary of the invention

[0005] The present invention is intended to provide a Se-doped Zintl phase thermoelectric material and a preparation method thereof, by doping Se element at the Te position of the thermoelectric material BaCu2Te2, the power factor of the material is improved, and the thermal conductivity of the material is further reduced, thereby optimizing the thermoelectric performance of the material and increasing the thermoelectric conversion efficiency. The problem in the background technology is solved.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a Se-doped Zintl phase thermoelectric material comprises the following steps:

[0008] S1. First, the Ba ingot is smelted to remove oxygen elements and impurities in the Ba ingot for purification;

[0009] S2. Weigh the Cu bars, Te blocks, Se powder and smelted Ba ingots in proportion in a glove box, cut the raw materials into pieces, put them into a crucible with a cover, and then put the crucible into a glass tube; wherein the ratio of Ba ingot, Cu bars, Te blocks and Se powder is 1:2:1.96:0.04;

[0010] S3, keeping argon gas in the glass tube, vacuum-sealing the glass tube, and placing it in a muffle furnace for solid-phase reaction;

[0011] S4. Take out the glass tube and put it into the glove box, take a sample, and grind it with a mortar to make the sample fully uniform and obtain a fine powder;

[0012] S6, putting the powder obtained in step S5 into a crucible, and then into a glass tube;

[0013] S7, keeping argon gas in the glass tube, vacuum-sealing the glass tube, and placing it in a muffle furnace for annealing;

[0014] S8. Take out the glass tube and put it into the glove box, take samples, and grind them with a mortar to make the samples fully uniform to obtain fine black powder. Sinter the powder into a solid by hot pressing to obtain the Zintl phase thermoelectric material BaCu2Te 1.96 Se 0.04 .

[0015] Further, in S4, the temperature setting of the solid phase reaction is specifically as follows: from room temperature to 450°C for 10 hours and keep warm for 10 hours, from 450°C to 600°C for 10 hours and keep warm for 10 hours, from 600°C to 900°C for 10 hours and keep warm for 3 days, and finally cooling to room temperature with the furnace.

[0016] Furthermore, in S7, the specific temperature and time of the annealing are: from room temperature to 750°C at a rate of 1.3°C / min and kept for 3 days, and finally cooled to room temperature in the furnace.

[0017] Furthermore, in S8, the hot pressing parameters are: pressure 75 MPa, temperature 600° C., and sintering time 35 min.

[0018] The Zintl phase thermoelectric material BaCu2Te is prepared by the method for preparing a Se-doped Zintl phase thermoelectric material as described above.1.96 Se 0.04 .

[0019] The beneficial effects of the technical solution are:

[0020] The present invention dopes 0.04 Se element at the Te position of BaCu2Te2 material. Since Se has stronger electronegativity than Te, after doping 0.04 Se atoms, electrons are provided to the material, thereby reducing the electrical conductivity of the material, making it reach the optimal carrier concentration range, and improving the Seebeck coefficient, thereby generally improving the power factor of the material, and achieving the purpose of improving electrical performance. After doping 0.04 Se element at the same time, due to the introduction of impurity atoms, phonon scattering is enhanced, the lattice thermal conductivity of the material is further reduced, and the thermal conductivity of the material is generally reduced, thereby achieving the purpose of reducing thermal performance. The enhancement of electrical performance and the reduction of thermal performance greatly improve ZT, and optimize the thermoelectric performance of Zintl phase BaCu2Te2 material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 1 is an XRD test result diagram of black powdered thermoelectric materials prepared in Examples 1 to 4 of the present invention and the comparative example;

[0022] Figure 2 is a graph showing changes in lattice constants of black powdered thermoelectric materials obtained in Examples 1 to 4 of the present invention and in a comparative example;

[0023] Figure 3 The thermoelectric material BaCu2Te obtained in Example 1 of the present invention 1.96 Se 0.04 SEM test results Figure 1 ;

[0024] Figure 4 The thermoelectric material BaCu2Te obtained in Example 1 of the present invention 1.96 Se 0.04 SEM test results Figure 2 ;

[0025] Figure 5 1 is a result diagram of the conductivity data of the thermoelectric materials prepared in Examples 1 to 4 of the present invention and the comparative example;

[0026] Figure 6 is a graph showing the Seebeck data results of thermoelectric materials prepared in Examples 1 to 4 of the present invention and in a comparative example;

[0027] Figure 7 1 is a result diagram of power factor data of thermoelectric materials prepared in Examples 1 to 4 of the present invention and in a comparative example;

[0028] Figure 8is a result diagram of total thermal conductivity data of thermoelectric materials prepared in Examples 1 to 4 of the present invention and in a comparative example;

[0029] Fig. 9 is a result diagram of lattice thermal conductivity data of thermoelectric materials prepared in Examples 1 to 4 of the present invention and in a comparative example;

[0030] Fig.10 It is a graph showing the ZT data results of thermoelectric materials prepared in Examples 1 to 4 of the present invention and the comparative example. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:

[0032] Example 1

[0033] A method for preparing a Se-doped Zintl phase thermoelectric material comprises the following steps:

[0034] S1. First, the Ba ingot is smelted to remove oxygen and impurities in the Ba ingot to achieve the purpose of purification for the next experiment. Since Ba metal is very easy to oxidize, it is best not to contact with air before and after smelting to avoid oxidation;

[0035] S2. Since Ba metal is very easy to oxidize, weighing and sampling are carried out in a glove box: the smelted Ba ingot, Cu bar, and Te block are weighed in proportion, the raw materials are cut into pieces, and Se powder is added to facilitate fusion, and then the samples are placed in a crucible with a lid, and then the crucible is placed in a glass tube. Among them, the ratio of Ba ingot, Cu bar, Te block and Se powder is 1:2:1.96:0.04;

[0036] S3. To avoid oxidation of the sample, a vacuum valve can be applied to the glass tube to isolate the air and keep the glass tube filled with argon. Then the glass tube is taken out of the glove box and vacuum sealed. The sealed glass tube is placed in a muffle furnace for solid phase reaction at 900°C. The specific temperature and time are as follows: from room temperature to 450°C for 10 hours and then kept at 450°C for 10 hours, from 450°C to 600°C for 10 hours and then kept at 600°C for 10 hours, from 600°C to 900°C for 3 days and then cooled to room temperature with the furnace.

[0037] S4. Considering that some raw materials may not react completely in one reaction, to avoid oxidation, put the taken out glass tube into the glove box, take out the sample in the crucible, and grind it with a mortar for half an hour to make the sample fully uniform and obtain a fine powder;

[0038] S6, putting the sample ground in step S5 back into the crucible, and then into the glass tube;

[0039] S7. Put a vacuum valve on the glass tube in the glove box, keep argon gas in the glass tube, take it out and seal it under vacuum, and put the sealed glass tube into a muffle furnace for annealing at a temperature of 750°C. The specific temperature and time are as follows: from room temperature to 750°C at a rate of 1.3°C / min and keep it for 3 days, and finally cool it to room temperature with the furnace;

[0040] S8. To avoid oxidation, the glass tube was placed in a glove box. The sample in the crucible was taken out and ground with a mortar for half an hour to make the sample more uniform and obtain a fine black powder. The powder was sintered into a solid by hot pressing to obtain the Zintl phase thermoelectric material BaCu2Te 1.96 Se 0.04 The hot pressing pressure is 75 MPa, the temperature is 600°C, and the sintering time is 35 min (the pressure should be removed immediately after the insulation).

[0041] Example 2

[0042] The difference between this example and Example 1 is that the ratio of Ba ingot, Cu strip, Te block and Se powder in this example is 1:2:1.98:0.02, and the Zintl phase thermoelectric material BaCu2Te 1.98 Se 0.02 ;

[0043] Example 3

[0044] The difference between this example and Example 1 is that the ratio of Ba ingot, Cu strip, Te block and Se powder in step S2 of this example is 1:2:1.94:0.06, and the Zintl phase thermoelectric material BaCu2Te 1.94 Se 0.06 ;

[0045] Example 4

[0046] The difference between this example and Example 1 is that the ratio of Ba ingot, Cu strip, Te block and Se powder in step S2 of this example is 1:2:1.92:0.08, and the Zintl phase thermoelectric material BaCu2Te 1.92 Se 0.08 ;

[0047] Comparative Example

[0048] The difference between this example and Example 1 is that the ratio of Ba ingot, Cu strip and Te block in step S2 of this example is 1:2:2, and the Zintl phase thermoelectric material BaCu2Te2 is obtained;

[0049] The fine black powdered thermoelectric material obtained in the above-mentioned Examples 1 to 4 and the comparative example step S8 was subjected to XRD test. The test results are as follows: Figure 1As shown, compared with the PDF card, the main peak matches well, and a few samples have miscellaneous peaks. When the main peak is enlarged, it is found that the main peak gradually shifts to the right. According to the Bragg formula, the sample unit cell gradually becomes smaller, which preliminarily proves that Se atoms enter the unit cell. Figure 2 The lattice constant diagram shows that as the doping concentration increases, the unit cell shrinks on the abc axis.

[0050] The thermoelectric material BaCu2Te obtained by doping Se0.04 in the above Example 1 1.96 Se 0.04 , SEM test is carried out, and the test results are as follows Figure 3 and Figure 4 As shown, Te, Cu, Ba, and Se elements are evenly distributed.

[0051] The Zintl phase thermoelectric materials obtained in the above-mentioned Examples 1 to 4 and the comparative example were tested for electrical properties such as conductivity, Seebeck and power factor. The test results are as follows: Figure 5 , Figure 6 and Figure 7 As shown, the sample material has good electrical properties and high electrical conductivity. The Seebeck coefficient increases with increasing temperature, resulting in a continuous increase in the power factor. The power factor of the doped sample is greatly improved compared to the base sample.

[0052] The Zintl phase thermoelectric materials obtained in the above-mentioned Examples 1 to 4 and the comparative example were subjected to thermal performance tests. The test results are as follows: Figure 8 and Fig. 9 As shown, the total thermal conductivity of the doped sample materials (except the 0.08 sample) is smaller than that of the base sample. In the lattice thermal conductivity diagram, the lattice thermal conductivity of the doped samples is smaller than that of the base sample, which is more conducive to improving the ZT value of the material. In particular, the Zintl phase thermoelectric material obtained by doping Se0.04 in Example 1 has the lowest total thermal conductivity and the lowest lattice thermal conductivity, and has excellent thermal performance.

[0053] Fig.10 The ZT values ​​of the Zintl phase thermoelectric materials obtained in Examples 1 to 4 and the comparative example show that the ZT values ​​of the doped samples are all greater than those of the matrix, among which the ZT value of the 0.04 sample is the highest, which is nearly doubled compared to the matrix. The above data show that BaCu2Te2 doped with Se is very beneficial to improving the thermoelectric performance of the material.

[0054] In summary, the present invention dopes 0.04 Se elements at the Te position of BaCu2Te2 material. Since Se has a stronger electronegativity than Te, 0.04 Se atoms are doped to provide electrons for the material, thereby reducing the electrical conductivity of the material, making it reach the optimal carrier concentration range, and at the same time improving the Seebeck coefficient, and generally improving the power factor of the material, achieving the purpose of improving electrical performance. At the same time, after doping 0.04 Se elements, due to the introduction of impurity atoms, phonon scattering is enhanced, the lattice thermal conductivity of the material is further reduced, and the thermal conductivity of the material is generally reduced, achieving the purpose of reducing thermal performance. The enhancement of electrical performance and the reduction of thermal performance greatly improve ZT and optimize the thermoelectric performance of Zintl phase BaCu2Te2 materials.

[0055] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a Se-doped Zintl phase thermoelectric material, characterized in that: The following steps are involved: S1. First, the Ba ingot is smelted to remove oxygen elements and impurities in the Ba ingot for purification; S2. Weigh the Cu bars, Te blocks, Se powder and smelted Ba ingots in proportion in a glove box, cut the raw materials into pieces, put them into a crucible with a cover, and then put the crucible into a glass tube; wherein the ratio of Ba ingot, Cu bars, Te blocks and Se powder is 1:2:1.96:0.04; S3, keeping argon gas in the glass tube, vacuum-sealing the glass tube, and placing it in a muffle furnace for solid-phase reaction; S4. Take out the glass tube and put it into the glove box, take out the sample, and grind it with a mortar to make the sample fully uniform and obtain a fine powder; S6, putting the powder obtained in step S5 into a crucible, and then into a glass tube; S7, keeping argon gas in the glass tube, vacuum-sealing the glass tube, and placing it in a muffle furnace for annealing; S8. Take out the glass tube and put it into the glove box, take samples, and grind them with a mortar to make the samples fully uniform to obtain fine black powder. Sinter the powder into a solid by hot pressing to obtain the Zintl phase thermoelectric material BaCu2Te 1.96 Se 0.04 .

2. The method for preparing a Se-doped Zintl phase thermoelectric material according to claim 1, characterized in that: In S4, the temperature setting of the solid phase reaction is specifically as follows: from room temperature to 450°C for 10h and keep warm for 10h, from 450°C to 600°C for 10h and keep warm for 10h, from 600°C to 900°C for 10h and keep warm for 3 days, and finally cooling to room temperature with the furnace.

3. The method for preparing a Se-doped Zintl phase thermoelectric material according to claim 1, characterized in that: In S7, the specific temperature and time of the annealing are: from room temperature to 750°C at 1.3°C / min and kept for 3 days, and finally cooled to room temperature in the furnace.

4. The method for preparing a Se-doped Zintl phase thermoelectric material according to claim 1, characterized in that: In S8, the hot pressing parameters are: pressure 75 MPa, temperature 600° C., and sintering time 35 min.

5. Se-doped Zintl phase thermoelectric material BaCu2Te prepared by the method for preparing a Se-doped Zintl phase thermoelectric material according to claim 1 1.96 Se 0.04 .